2011
DOI: 10.3892/ijmm.2011.717
|View full text |Cite
|
Sign up to set email alerts
|

Novel monoclonal antibodies against pancreatic juice from pancreatic cancer patients and their possible application in differential diagnosis

Abstract: Abstract. Pancreatic cancer (PC) has a poor clinical prognosis with a <10% 5-year survival rate. Because there are no specific biomarkers of PC, it is difficult to detect small PC tumors and most patients are diagnosed at an advanced stage. Specific biomarkers are useful tools for the early detection of cancer. However, PC-related biomarkers, such as CA19-9 lack specificity and sensitivity. In this study, we took an immunological approach to establish novel monoclonal antibodies (mAbs) specific for the pancrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Almost 20 y after this technique was described, Hamabashiri et al . 8 produced 4 mAbs (2P-1–2–1, 2P-1–17–1, 6P-3–2–4 and 7P-9–11–6) specific to pancreatic juice from cancer patients, which have a potential application for differential diagnosis. Their immunization protocol was performed using female BALB/c mice, 5–6 weeks old, tolerized with 25 µg of inflammatory pancreatic juice diluted in phosphate-buffered saline (PBS) and adjuvant.…”
Section: Drug-induced Subtractive Immunizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Almost 20 y after this technique was described, Hamabashiri et al . 8 produced 4 mAbs (2P-1–2–1, 2P-1–17–1, 6P-3–2–4 and 7P-9–11–6) specific to pancreatic juice from cancer patients, which have a potential application for differential diagnosis. Their immunization protocol was performed using female BALB/c mice, 5–6 weeks old, tolerized with 25 µg of inflammatory pancreatic juice diluted in phosphate-buffered saline (PBS) and adjuvant.…”
Section: Drug-induced Subtractive Immunizationmentioning
confidence: 99%
“…Hamabashiri et al. 8 showed that their approach is an effective technique to obtain specific mAbs to rare or poor immunogenic antigens, and that it can be used to provide tools for new strategies in the premature diagnosis of cancer.…”
Section: Drug-induced Subtractive Immunizationmentioning
confidence: 99%